2018
DOI: 10.1038/s41433-018-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volume of various retinal layers over time in early and intermediate age-related macular degeneration

Abstract: Purpose To evaluate longitudinally volume changes in inner and outer retinal layers in early and intermediate age-related macular degeneration (AMD) compared to healthy control eyes using optical coherence tomography (OCT). Methods 71 eyes with AMD and 31 control eyes were imaged at two time points: baseline and after 2 years. Automated OCT layer segmentation was performed using Orion TM. This software is able to measure volumes of retinal layers with distinct boundaries including Retinal Nerve Fibre Layer (RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 31 publications
9
48
1
Order By: Relevance
“…For example, reduced thickness of the retinal ganglion cell complex (GCC; a composite retinal layer comprising the retinal layers containing the ganglion cell dendritic synapses with bipolar and amacrine cells, the ganglion cell bodies, and the ganglion cell axons viz., the IPL, GCL, and NFL respectively) has also been associated with a variety of ocular diseases in their early stages, such as glaucoma [56], retinal vessel loss in open-angle glaucoma [57], and chiasmal compression [58]. Similar changes have also been reported in early age-related macular degeneration [59]. This highlights the sensitivity of these layers to a variety of pathologies and also indicates the need to control for these conditions, where possible, in future analyses.…”
Section: Discussionmentioning
confidence: 56%
“…For example, reduced thickness of the retinal ganglion cell complex (GCC; a composite retinal layer comprising the retinal layers containing the ganglion cell dendritic synapses with bipolar and amacrine cells, the ganglion cell bodies, and the ganglion cell axons viz., the IPL, GCL, and NFL respectively) has also been associated with a variety of ocular diseases in their early stages, such as glaucoma [56], retinal vessel loss in open-angle glaucoma [57], and chiasmal compression [58]. Similar changes have also been reported in early age-related macular degeneration [59]. This highlights the sensitivity of these layers to a variety of pathologies and also indicates the need to control for these conditions, where possible, in future analyses.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the results obtained from the custom built UHR-OCT may limit the generalization of our current findings. However, the Orion Software used in the present study has been adapted in commercial OCT devices such as Zeiss Cirrus HD-OCT (with special data exportation), 44,45 Topcon 3D-1000 (Topcon Medical Systems, Inc., Oakland, NJ, USA), 46 and Spectralis SD OCT (Heidelberg Engineering, Heidelberg, Germany). 47 Our study can be repeated using these commercial OCT devices and the Orion software.…”
Section: Discussionmentioning
confidence: 99%
“…47 Our study can be repeated using these commercial OCT devices and the Orion software. [44][45][46][47] In addition, the visualized thickness reduction patterns may provide a reference for the clinical interpretation of OCT images using clinically available OCT devices. Third, the segmentation of intraretinal layers of each B-scan of the volumetric data set was not verified by the investigators, which constitutes a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown changes in GCL thickness within a smaller macula area and with less dense spatial sampling. 9,[11][12][13][14][15]20,21 Both GCL thinning and thickening were observed in AMD eyes, with the latter more common. In support of our findings, GCL thickening has been reported recently by Brandl et al 21 in mild-early AMD (Three Continent AMD Consortium classification).…”
Section: The Majority Of Amd Eyes Exhibit Significant Gcl Changesmentioning
confidence: 99%
“…Of other previous literature, most actually contrast our work and Brandl's, suggesting GCL thinning to be more common in nonexudative AMD. The majority of these studies, however, have only implied GCL thinning as a component of the GCL-IPL complex thinning, [11][12][13][14][15]20 and have a number of other limitations, including small sample sizes, [11][12][13][14][15] a lack of age-matching, 12,13,15 auto-segmentation, [11][12][13][14][15]20 which has shown poorer variability compared to manual correction, 37 and less specific spatial analyses. 13,20 Our study accounted for these limitations by including a large sample size with age-matching, manual correction of segmentation when required, and a locationspecific methodology using grid analysis alongside macula spatial clusters, which have proven robust structure-function concordance.…”
Section: The Majority Of Amd Eyes Exhibit Significant Gcl Changesmentioning
confidence: 99%